The emergence of extracellular vesicles in urology: fertility, cancer, biomarkers and targeted pharmacotherapy. Issue 1 (30th June 2015) - Tompkins, Andrew J.; Chatterjee, Devasis; Maddox, Michael; Wang, Justin; Arciero, Emily; Camussi, Giovanni; Quesenberry, Peter J.; Renzulli, Joseph F.
Abstract : Extracellular vesicles (EV) are small membrane‐bound vesicles enriched in a selective repertoire of mRNA, miRNA, proteins and cell surface receptors from parental cells and are actively involved in the transmission of inter and intracellular signals. Cancer cells produce EV that contain cargo including DNA, mRNA, miRNA and proteins that allow EV to create epigenetic changes in target cells both locally and systemically. Cancer‐derived EV play critical roles in tumorigenesis, cancer cell migration, metastasis, evasion of host immune defense, chemoresistance, and they promote a premetastatic niche favourable to micrometastatic seeding. Their unique molecular profiles acquired from originator cells and their presence in numerous body fluids, including blood and urine, make them promising candidates as biomarkers for prostate, renal and bladder cancers. EV may ultimately serve as targets for therapy and as platforms for personalized medicine in urology. As urologic malignancy comprises 28% of new solid tumour diagnoses and 15% of cancer‐related deaths, EV‐related research is rapidly emerging and providing unique insights into disease progression. In this report, we review the current literature on EV in the setting of genitourinary fertility and malignancy.